L'enquête publique préalable à la décision comme modèle alternatif - Colson, Jean-Philippe (Les Cahiers de droit, 1983)
This paper surveys the present state of French law concerning local inquiries on works projects in the energy sector, such as dams, power plants, transmission lines, etc. This is done in the light of the Democratization of Inquiries Bill, which received first reading in the French National Assembly in April, 1983. The subject is treated from three points of view : the scope of application of the inquiry procedure ; the inquiry process itself ; and its effectiveness as a means towards citizens's involvement in public decisionmaking. As regards the scope of the procedure, the Bill would extend it somewhat beyond the cumulative scope of the several existing types of inquiry. Any project affecting the environment would normally be subjected to be the inquiry procedure. As regards the inquiry process itself the Bill would strengthen the independence of inquiry commissioners in that it gives them broader investigative powers, allows them to hold contradictory public hearings upon request albeit with the agreement of the decision-making authority, and requires them to publish reports, with reasons of each inquiry. As regards the effectiveness of the procedure, the Bill would make it easier for dissatisfied parties to obtain a injunction restraining the implementation of a project if the commissioner had reported against it. On the whole, the Bill seems to promise significant improvements in the inquiry process, particularly as it provides for contradictory debate, including the consideration of alternative proposals. However, it leaves open a number of questions about the real purpose served by the procedure and about the proper timing of the inquiry in the total decision-making process.